2019
DOI: 10.1111/and.13254
|View full text |Cite
|
Sign up to set email alerts
|

Sperm agglutination: Prevalence and contributory factors

Abstract: Agglutination is a finding noted in semen analyses (SAs) that often causes confusion as to its significance. While some have attributed agglutination to antisperm antibodies (ASAs), there are other causes as well, such as genital tract infection and ascorbic acid deficiency. Additionally, it is known that patients with ASAs often have risk factors such as a history of scrotal trauma or surgery. Therefore, we sought to determine the prevalence of agglutination in our patient population and correlate it with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 20 publications
(25 reference statements)
0
19
0
1
Order By: Relevance
“…Compared to the tests described above, the IBT test has a number of advantages, such as the ability to determine the isotype of ASAs, their localization, also it has high sensitivity and specificity [24,153,154]. The WHO recommended both MAR and IBT tests as screening methods for ASAs reveal [7,11,35,[120][121][122]155]. The MAR test is considered sufficient because IgA almost never occurs without IgG, and, as it was already mentioned, there is a variant of the Sperm MAR test that can detect IgA associated with sperm [24].…”
Section: Methods Of Asas Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the tests described above, the IBT test has a number of advantages, such as the ability to determine the isotype of ASAs, their localization, also it has high sensitivity and specificity [24,153,154]. The WHO recommended both MAR and IBT tests as screening methods for ASAs reveal [7,11,35,[120][121][122]155]. The MAR test is considered sufficient because IgA almost never occurs without IgG, and, as it was already mentioned, there is a variant of the Sperm MAR test that can detect IgA associated with sperm [24].…”
Section: Methods Of Asas Detectionmentioning
confidence: 99%
“…In general, infectious processes can disrupt local immune regulation, can damage spermatozoa directly or through an inflammatory reaction, leading to the formation of ASAs [122]. It was found that in more than 40% of cases, ASAs to sperm surface antigens were found in infected patients, which is significantly higher rate than among uninfected infertile and fertile men [126].…”
Section: Anti-sperm Autoimmunity and Infection: Essential Triggermentioning
confidence: 99%
See 1 more Smart Citation
“…The ASA test is recommended to patients with asthenozoospermia, with disrupted blood-testis barrier, or when sperm agglutination can be observed during a routine semen analysis (Snow-Lisy & Sabanegh, 2013). One of the causes for sperm agglutination is the presence of ASA (Berger, Smith-Harrison, & Sandlow, 2019). ASA in the serum and seminal plasma can lead to male infertility by interfering with sperm motility and sperm-oocyte binding (Agarwal & Said, 2009;Chiu & Chamley, 2004) and incapacity of penetrating the cervical mucus (De Almeida, Soumah, & Jouannet, 1986 (Mazumdar & Levine, 1998).…”
Section: Anti-sperm Antibodies Testmentioning
confidence: 99%
“…Researchers provided evidence that antibody-mediated immune reactions were responsible for spontaneous or missed abortions [152,153]. Missed abortion is a term used for a spontaneous abortion due to fetal demise without any extraneous intervention.…”
Section: Role Of Antisperm Antibodies In Pregnancymentioning
confidence: 99%